Reticulation on ground floor, David Sassoon Clock Tower - Ghosh, Ayan (2023)
The same year David Sassoon funded the clock tower at Victoria Gardens, he constructed the Magen David Synagogue in Byculla, which also features a clock tower. Another clock tower would feature at the Sassoon Docks, completed in 1875. The David Sassoon Library & Reading Room also has a large clock, though not installed in a separate clock tower.